Role of antenatal care in reducing incidence of eclampsia in eastern Uttar Pradesh, India - Kapoor, Babita; Verma, Namrata; Shrivastava, Reena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Eclampsia is characterized by sudden onset of generalized tonic-clonic convulsions or coma in pregnancy or postpartum. It is a major cause of maternal and perinatal morbidity and mortality in developing countries. This study was conducted to determine the incidence of eclampsia and role of antenatal care in reducing the incidence. Methods: This was a prospective study (July 2015-June 2016) conducted in labour room of department of obstetrics and Gynecology, BRD Medical college, Gorakhpur, Uttar Pradesh, India. A total no. of 141 women presenting with eclampsia were included in the study. Risk factors like antenatal care and sociodemographic status were studied for their role in increased incidence of eclampsia. Results: There were 141 eclampsia cases out of 3536 deliveries, during the study period. The incidence of eclampsia was found to be 4%. Out of 141 eclampsia cases 35.5% did not receive any antenatal care. 56.7% received substandard care in less than 4 antenatal visits. Out of those who received antenatal care (91/141), 67% received irregular, substandard care in primary health centre of their locality. Majority of eclampsia cases were between 16-25 years of age (85.1%) and were primigravida (62.4%). Majority of eclampsia cases were uneducated (89.4%), of lower socioeconomic status (71.4%) and belonged to rural area (67.4%). Conclusions: High incidence of eclampsia in B.R.D. Medical College reflects the status of eclampsia in eastern Uttar Pradesh, India. To prevent eclampsia our health care centres should be strengthened by well trained medical officers, other health care workers and adequate antenatal care facilities.